PENILAIAN BAHAN AJAR BAHASA MADURA TINGKAT SEKOLAH MENENGAH ATAS (SMA) - Kusyairi, M. Khoiri dan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2019)
The purpose of this study was to find out information and describe the quality of Madurese language teaching materials both in terms of content, presentation, and language. The type of this research is development research, namely by conducting a high school level Madura curriculum curriculum (syllabus) study as well as research instruments given to students and material experts who subsequently produce teaching materials. The results of the study showed that the students' response to the Madura language teaching material at the high school level was in the valid category and could be used but needed a small revision, with a value of 70.64. Whereas the results of the material expert validation state that Madurese language teaching materials in the category are less valid and can be used but need revision, with a value of 66.88.